2020
DOI: 10.1103/physrevb.101.075115
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb correlation in noncollinear antiferromagnetic α -Mn

Abstract: We discuss the interplay between magnetic and structural degrees of freedom in elemental Mn. The equilibrium volume is shown to be sensitive to magnetic interactions between the Mn atoms. While the standard generalized-gradient-approximation underestimates the equilibrium volume, a more accurate treatment of the effects of electronic localization and magnetism is found to solve this longstanding problem. Our calculations also reveal the presence of a magnetic phase in strained α-Mn that has been reported previ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…The sizes of local magnetic moments largely depend on the types of Mn-sites according to experiments in the AFM phase at ambient pressure. The magnetic moments on Mn-I and -II sites are quite larger than those on Mn-III and -IV sites, as shown in Table III [43][44][45] and a similar tendency for local magnetic moments is obtained by the first-principles calculations [49][50][51][52]. In addition, the internal magnetic fields on Mn-III and -IV sites are rapidly suppressed by an applied pressure TABLE III.…”
Section: Application To Representative Ahe Antiferromagnets a α-Mnsupporting
confidence: 67%
“…The sizes of local magnetic moments largely depend on the types of Mn-sites according to experiments in the AFM phase at ambient pressure. The magnetic moments on Mn-I and -II sites are quite larger than those on Mn-III and -IV sites, as shown in Table III [43][44][45] and a similar tendency for local magnetic moments is obtained by the first-principles calculations [49][50][51][52]. In addition, the internal magnetic fields on Mn-III and -IV sites are rapidly suppressed by an applied pressure TABLE III.…”
Section: Application To Representative Ahe Antiferromagnets a α-Mnsupporting
confidence: 67%
“…For example, by using schemes beyond GGA in YBa 2 Cu 3 O 7 55 , new landscape of solutions characterized by stripe orders with large magnetic moments on Cu atoms have been recently uncovered. Similarly, one has found that the energy minimization with the same DFT scheme beyond the GGA is controlled by large Mn local moments in elemental manganese 68 . These observations demonstrate that correlation effects enable a new generation of understanding of the large magnetic shape memory effect, and how this property emerges through the interplay of spin, charge, and lattice degrees of freedom.…”
Section: Discussionmentioning
confidence: 86%
“…"Strong correlation" is sometimes used to mean "everything that DFT gets wrong." Yet, hybrid functionals (including part of the Hartree-Fock exchange) like HSE06 (8-10) (for nonmetallic states) and meta-generalized gradient approximations (meta-GGAs) like the strongly constrained and appropriately normed (SCAN) functional (4,(11)(12)(13)(14)(15)(16)(17)(18) are yielding quantitatively correct ground-state (and we emphasize "ground-state") results by symmetry breaking for some systems that have long been regarded as strongly correlated. In the cuprate high-temperature superconducting materials, for example, the SCAN meta-GGA (4) is able to do what simpler density functionals (local spin density approximation [LSDA] and generalized gradient approximation [GGA]) cannot (13), by creating the correct spin moments on the copper atoms, their antiferromagnetic order, and a correctly nonzero band gap in the undoped material that correctly disappears under the doping that also leads to superconductivity (12)(13)(14).…”
Section: Significancementioning
confidence: 99%